2013
DOI: 10.1007/s12010-013-0559-6
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Tetracycline Under Various Conditions and Effects on Microbial Community

Abstract: Five hundred tons of antibiotics are consumed yearly in the world. In this study, the biodegradation characteristics of tetracycline (TET) under nitrate-reducing, sulfate-reducing, and methanogenic conditions were determined by batch tests. Also, effects of TET on mixed microbial cultures were revealed by microbiological analysis. In this scope, gas generation and composition, dissolved organic carbon, and electron acceptor concentrations were monitored during 120 days. Additionally, changes on quantities of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…As the 4-epimer was included in the quantification, the elimination cannot be attributed to epimerization. Cetecioglu et al found a biodegradation rate of 46% for tetracycline under methanogenic conditions (Cetecioglu et al, 2014). The authors suggested that the elimination respective mineralization might be lower in a full-scale reactor due to differences in the ionic strength of the matrices.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…As the 4-epimer was included in the quantification, the elimination cannot be attributed to epimerization. Cetecioglu et al found a biodegradation rate of 46% for tetracycline under methanogenic conditions (Cetecioglu et al, 2014). The authors suggested that the elimination respective mineralization might be lower in a full-scale reactor due to differences in the ionic strength of the matrices.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…However, even though antibiotics are inhibitory for bacteria, they are also biologically degradable. For example, tetracycline was found to be biodegradable under methanogenic conditions [13]. Thus, anaerobic digestion, under methanogenic conditions, of antibiotic containing manure can be beneficial since it decreases antibiotic concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Total COD input (0.69 g per sampling event) was the same across all four digesters except for R4, which had 0.21% higher COD input than the other reactors. This is due to the addition of 20 mg/L TC-HCl, which could have served as a potential substrate as shown from earlier studies that demonstrated the biodegradability of TC (Álvarez et al 2010; Cetecioglu et al 2014). COD converted to biomass was calculated based on sludge wasted per sampling event, average microbial degradation/regeneration rates, and biomass accumulated.…”
Section: Resultsmentioning
confidence: 96%